Let's solve the equation step by step, filling in the missing terms and descriptions as requested.
Given Equation: \( 16w + 9 = 13w + 18 \)
Step 1:
Subtract \( 13w \) from both sides.
- Description: Subtract 13w from both sides
\[ 16w - 13w + 9 = 18 \]
\[ 3w + 9 = 18 \]
Step 2:
Subtract 9 from both sides.
- Description: Subtract 9 from both sides
\[ 3w + 9 - 9 = 18 - 9 \]
\[ 3w = 9 \]
Step 3:
Divide both sides by 3.
- Description: Divide both sides by 3
\[ \frac{3w}{3} = \frac{9}{3} \]
\[ w = 3 \]
Now let's summarize:
- Start with the equation \( 16w + 9 = 13w + 18 \)
- Subtract \( 13w \) from both sides → \( 3w + 9 = 18 \)
- Subtract 9 from both sides → \( 3w = 9 \)
- Divide both sides by 3 → \( w = 3 \)
So the complete solution is:
- \( 3w = 9 \)
- \( w = 3 \)
Descriptions filled in:
- Subtract 13w from both sides
- Subtract 9 from both sides
- Divide both sides by 3